2014
DOI: 10.1158/0008-5472.can-13-3569
|View full text |Cite
|
Sign up to set email alerts
|

Hippo Coactivator YAP1 Upregulates SOX9 and Endows Esophageal Cancer Cells with Stem-like Properties

Abstract: Cancer stem cells are proposed to initiate and maintain tumor growth. Deregulation of normal stem cell signaling may lead to the generation of cancer stem cells (CSCs); however, the molecular determinants of this process remain poorly understood. Here we show that the transcriptional co-activator YAP1 is a major determinant of CSC properties in non-transformed cells and in esophageal cancer cells by direct upregulation of SOX9. YAP1 regulates the transcription of SOX9 through a conserved TEAD binding site in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
235
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 235 publications
(249 citation statements)
references
References 41 publications
12
235
1
1
Order By: Relevance
“…Indeed, Liu-Chittenden et al screened a small-molecule library (consisting of 3,300 FDA-approved drugs) for agents that inhibit YAP-TEAD activity in a cell-based assay (72). Verteporfin was identified to be a compound effective at preventing hepatic tumorigenesis driven by YAP overexpression (72) and the growth of xenograft tumors in immunodeficient mice (52,74). Thus, administration of verteporfin is an effective pharmacologic approach to inhibit YAP signaling, and these studies strongly support the feasibility of targeting YAP in human cancer in which Hippo-YAP is deregulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Liu-Chittenden et al screened a small-molecule library (consisting of 3,300 FDA-approved drugs) for agents that inhibit YAP-TEAD activity in a cell-based assay (72). Verteporfin was identified to be a compound effective at preventing hepatic tumorigenesis driven by YAP overexpression (72) and the growth of xenograft tumors in immunodeficient mice (52,74). Thus, administration of verteporfin is an effective pharmacologic approach to inhibit YAP signaling, and these studies strongly support the feasibility of targeting YAP in human cancer in which Hippo-YAP is deregulated.…”
Section: Discussionmentioning
confidence: 99%
“…and K.F.). Both the YAP staining intensity (a scale of from 0 to 3 was used, where 0 is negative, 1 is weak staining, 2 is moderate staining, and 3 is strong staining) and nuclear localization (the percentage of tumor cell nuclei stained, where 0 is no staining, 1 is Յ10% of tumor cell nuclei stained, 2 is 10 to 50% stained, and 3 is Ͼ50% stained) were scored (52).…”
mentioning
confidence: 99%
“…Thus, the YAP/TAZ-induced transcriptional program may influence tumor-initiating properties that are associated with aggressive OSCC. Additional transcription factors implicated in cancer progression were also regulated by YAP/TAZ, including SOX9, which has recently been described as a target of YAP in esophageal cancers (45). Notably, members of the TEAD family were induced by YAP/TAZ, and increased expression of TEAD4 was significantly elevated with increased OSCC grade and stage.…”
Section: Discussionmentioning
confidence: 99%
“…Profoundly, VP abrogates liver overgrowth induced by YAP over-expression in vivo, verifying the therapeutic potential of targeting YAP-TEAD interaction. More recently, it was demonstrated that VP inhibits esophageal cancer development in vivo by down-regulating SOX9, another YAP-TEAD target gene [108]. Simvastatin, which is originally prescribed to reduce cholesterol in patients with cardiovascular disease, is recently found to inhibit YAP-TEAD activity and leads to suppression of RHAMM transcription in breast cancer cells [107].…”
Section: Yap-targeted Cancer Therapymentioning
confidence: 99%